Π‐Concave Hosts for Curved Carbon Nanomaterials. Issue 27 (12th March 2019) - Selmani, Serxho; Schipper, Derek J.
Abstract: Carbon nanomaterials have been at the forefront of nanotechnology since its inception. At the heart of this research are the curved carbon nanomaterial families: fullerenes and carbon nanotubes. While both have incredible properties that have been capitalized upon in a wide variety of applications, there is an aspect that is not commonly exploited by nanoscientists and organic chemists alike: the interaction of curved carbon nanomaterials with curved organic small molecules. By taking advantage of these interactions, new avenues are opened for the use of fullerenes and carbon nanotubes. Abstract : Sorting carbon nanomaterials requires more than a deft hand. Through the use of shape complimentary π‐concave host molecules, significant strides have been made in the purification and sorting of fullerenes and carbon nanotubes. Even more importantly, the use of π‐concave molecules can open up these carbon nanomaterials to new and exciting applications through their reversible binding, which leaves the electronic structures of these nanomaterials largely unaltered. However, to use π‐concave molecules to great effect, it is imperative to understand what constitutes effective design.